O trabalhador da educação e a acumulação flexível do capital: um estudo do posicionamento do Sintego frente à política educacional de Goiás - Araujo Júnior, João Ferreira de (2013)
This study aims to understand the "understanding and positioning" of Sintego regarding changes in pedagogical work, since the implementation of the "Pact for Education: a better future requires changes" in the State of Goiás. It was developed in the Research Line “Education, Labor and Social Movement”, of the Post-Graduation Program in FE/UFG. Transformations in the world of work and actions of the Education Workers Union of the State of Goiás (SINTEGO) were adopted as a theoretical framework to understand the educational project of the State of Goiás. This work was based theoretically on the following authors: Harvey (2011), Cruz (2005; 2008), Corràgio (1999), Schwartzman and Cox (2009), Saviani (1991; 2009; 2012), Paro (1993; 2010; 2011), Enguita (1989), Tumolo and Bez (2008), Canezin (2009) e Boito Jr. (1996; 1999; 2001; 2005). Semistructured interviews with the direction of Sintego were achieved for data collection. Searches for theses, dissertations and articles on the bank of theses and dissertations of Federal University of Goiás (UFG), Federal University of Brasilia (UNB), PUC-GO and database CAPES in journals of education, produced between the years 1990-2011, were searched. Pact for Education was understood as governance project, disseminated by international organizations, in the flexible accumulation of capital, which aims to expand the privatization of the public. In this displacement of borders between public and private, relations and conditions of educational work were changed, requiring new struggles and workers' organizations. As result of the research, it was found that Sintego knows the process of expanding the private sector in the provision of public educational services. However, it still could not make this process becomes a battle flag, getting stuck in specific fights, based on factors external to the process and outcome of pedagogical work.